PROBLEMS AND PROSPECTS OF GEOMETRIC AND GRAPHIC EDUCATION AT A TECHNICAL UNIVERSITY (World Bulletin of Social Sciences, 2024)
This article discusses the problems and prospects of graphic education at a technical university.